First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Diagnostics of the solar activity influence on the global atmospheric circulation in the thermosphere and MLT area: wave—mean flow interaction effects - Andrey V. Koval; Kseniia A. Didenko; Tatiana S. Ermakova; Nikolai M. Gavrilov; Anastasia G. Golovko (Climate Dynamics, 2025)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Using accelerometry to quantify prey attack and handling behaviours in piscivorous pike Esox lucius - M. Van Deurs; A. Andersson; J. Vinterstare; A. Didenko; A. Persson; C. Brönmark; P. A. Nilsson (Journal of Fish Biology, 2017)
Accelerometer technology was used to evaluate behaviours in the teleost ambush predator pike Esox lucius foraging on crucian carp Carassius carassius . Automated rule‐based estimates of prey‐size determined handling time were obtained and are compared with video‐recorded behaviours. Solutions to tag attachment and the limitations imposed by battery‐time and data‐logging capacities are evaluated.

Colonization by Staphylococcus aureus of Nano-Structured Fluorinated Surfaces, Formed by Different Methods of Ion-Plasma Technology - V. M. Elinson; L. V. Didenko; N. V. Shevlyagina; G. A. Avtandilov; A. Kh. Gaidarova; A. N. Lyamin (Bulletin of Experimental Biology and Medicine, 2016)

Morphofunctional changes in guinea pig ovaries in experimental chronic herpesvirus infection - N. V. Shevlyagina; A. M. Ivanova; T. G. Borovaya; L. V. Didenko; L. K. Berezina; A. N. Narovlyansky; F. I. Ershov (Bulletin of Experimental Biology and Medicine, 2008)